(untitled) (EU and comparative law issues and challenges series (ECLIC), 2018)
The National Assembly of the Republic of Serbia enacted the National Judicial Reform Strategy for the period from 2013 to 2018 in 2013 and the Government adopted an Action plan for implementation of the National Judicial Reform Strategy in which it envisages concrete measures and activities for implementation of strategic objectives, defines the deadlines and competent authorities for its implementation and financial sources. The Republic of Serbia accepted the EU Acquis with respect to Chapter 23 Judiciary and Fundamental Rights in 2016. On the path of EU integration, the constitutional reform of the judiciary is a very important and necessary step. Serbian constitutional law experts as well as the Venice Commission identified a number of weak points of the Constitution of Serbia of 2006 regarding the judicial system. Those weak points compromised the possibility of adhering to the principle of judicial independence as one of the basic principles of the rule of law. In this article, the author explains what should be regulated in the Constitution in order to have stronger guarantees of independence of the judiciary and the rule of law. Bearing in mind that there is no uniform European model of judiciary, the author concludes that successful constitutional reform requires a compromise between executive power and its tendency to dominate judiciary, on the one hand, and judicial power and its aspiration for absolute independence, on the other hand.